Gastropoda community structure in the mangrove forest of Ketapang Coastal Waters, Rupat District - Rivaldi, Rahmat; Nasution, Syafruddin; Efriyeldi, Efriyeldi (Science, Technology, and Education Care, 2024)
Gastropod community structure is a concept or study that studies the arrangement or composition of species in an ecosystem. Changes influence the structure of this gastropod community in terms of environmental factors such as temperature, salinity, substrate type, and organic matter content. Rupat District is geographically located in a cluster of islands directly adjacent to the Strait of Malacca, strongly influenced by coastal environmental conditions. Rupat sub-district has one of three tropical marine ecosystems, namely mangroves. This study aims to determine the structure of gastropod communities in mangrove forests in Ketapang Beach, Rupat District waters. The study was conducted in April 2023 using the technique of random sampling with a total of three stations. There are 8 (eight) species of gastropods found, with the species Cerithidea obtusa the dominant one. The abundance of gastropods is 130,000 ind/ha. The value of the diversity index (H') is 1.24, the uniformity index (E) is 0.33, and the dominance index value (C) is 0.40. The distribution pattern (Id) is grouping. The similarity index (Ss) of gastropods between each station in Ketapang Beach is almost the same type and has similarities that are classified as high category. Test results Oneway ANOVA < 0.05. The LSD (Least Significance Difference) test states that the abundance between stations I and III is significant, just as stations II and III are markedly different. The abundance between station I and station II does not differ markedly.